Bandos armados nas Minas Gerais : redutos de dominação bandoleira e poder local nos sertões mineiros setecentistas (1760-1808) - Rodrigo Leonardo de Sousa Oliveira (2014)
This research aimed to the study of legislation on banditry in Portugal and Mines and the actions of gangs of prey who worked in the mining captaincy. In general, we demonstrate how it is possible, through these studies, cooperate with current studies on local government in Portuguese America, since there was the formation of powerful client networks that linked bandits and potentates in the backlands of the "Gerais". This led to the strengthening of the "Territórios de Mando" and the formation of the "Redutos de dominação Bandoleira" in these barren areas and little policed by the authorities.